1977
DOI: 10.1111/j.1469-7998.1977.tb03916.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Red band fish, Cepola rubescens

Abstract: With 4 plates and 3 figures in the text)The burrows of the Red band fish, Cepola rubescens L. are described from casts taken in situ using polyester resin. Observations of behaviour and spatial distribution are presented and the coloration, morphology, age, gonad condition and diet of captured specimens are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
5
Order By: Relevance
“…Bay of Biscay; Loch Torridon, Scotland; Fishguard harbour, South Wales) and even interspecific connections between burrows are known, e.g. between the angular crab and the mud shrimp (Atkinson et al 1977) or the angular crab and the Norway lobster (Atkinson 1974). Trenkel et al (2007) found that direct competition between the angular crab and the Norway lobster seems to be reduced by different diurnal activity patterns in the Bay of Biscay.…”
Section: Discussionmentioning
confidence: 99%
“…Bay of Biscay; Loch Torridon, Scotland; Fishguard harbour, South Wales) and even interspecific connections between burrows are known, e.g. between the angular crab and the mud shrimp (Atkinson et al 1977) or the angular crab and the Norway lobster (Atkinson 1974). Trenkel et al (2007) found that direct competition between the angular crab and the Norway lobster seems to be reduced by different diurnal activity patterns in the Bay of Biscay.…”
Section: Discussionmentioning
confidence: 99%
“…Kaya et al. (2001) reported that the oldest specimen from the Izmir Bay was 5 years old, while Atkinson and Pullin (1976) noted 5‐year‐old specimens in Lundy (England). The observed total length L t = 55.5 cm in this study is the maximum observed value in the Adriatic; the previous value was L t = 54.0 cm (Jardas, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour, feeding, age, growth, mortality, sex ratio, spawning season, size at maturity and fisheries aspects of red bandfish have been studied thoroughly in various areas of its distribution (Vives et al., 1959; Atkinson et al., 1977; Bridges et al., 1982; Isola and Relini, 1984; Stergiou et al., 1992, 1996; Stergiou, 1993a,b; Stergiou and Papaconstantinou, 1993). However, published information on its biology and ecology in the Adriatic Sea is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The stomachs of bandfi sh from Ebro estuary contained also deep-water plankton species. Other studies-conducted by Atkinson (1976) and Atkinson et al (1977) in the Bristol Channel (12 m of depth) and covering one and 10 fi sh specimens, respectively-revealed that the dominant food items were copepods (Calanus helgolandicus, Centropages typicus, Temora longicornis, and Candacia armata). Few other food items, such as euphausiids, chaetognaths (Sagitta spp.…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with the results of Stergiou (1993), who concluded that, red bandfi sh food preference changes according to the abundance of the plankton rather than the size of planktonic organisms. According to Vives et al (1959) and Atkinson (1977) there was a relation between the composition of zooplankton found in the stomach contents of the red bandfi sh and the depth they inhabit.…”
Section: Discussionmentioning
confidence: 99%